Morar online: a emergência das plataformas de mercado imobiliário e a locação residencial no município de São Paulo - Batista, Lucas Meirelles Toledo Ramos (2021)
The recent performance of platforms in Real Estate makes necessary a deeper understanding of this phenomenon given the potentially disruptive impact that this kind of business has. The current perspectives in the literature about platforms, whether the market or engineering design, present meaningful contributions to the discussion of this phenomenon but do not provide us with a broader understanding of it when analyzing the real estate sector and the production of space. Therefore, it is necessary to incorporate concepts and references from areas such as urban planning and urban geography, expanding the theoretical framework. Through the approximation of these theoretical references, this master's thesis aims to identify the architecture of these ecosystems, the main mechanisms adopted by them for the generation of value, and their financing. The applied methodology is the comparative geospatial analysis based on spatial auto-correlation indicators and spatial dependence models. Using data obtained through an automated collection, combined with secondary data from the IBGE Demographic Census, this research seeks to identify the spatiality of this phenomenon, contributing to the growing debate in the field in the eyes of a Latin American metropolis. The primary purpose of this dissertation is to discuss how Platforms Real State are configured in the city of São Paulo and what differentiates them from traditional real estate firms—presenting what they differ in terms of area of operation, typology and rental price based on an exploratory data analysis. Differences were observed at all points, and for each of them, the main explanation possibilities were described. It is concluded that real estate market platforms, even though they represent a smaller universe than traditional real estate companies, affect the price of housing and are included in recent real estate production in the city of São Paulo.